Self‐esteem and learning dynamics in nursing students: An existential‐phenomenological study - Jacinthe Dancot; Benoît Pétré; Bernard Voz; Pascal Detroz; Rémi Gagnayre; Jean‐Marc Triffaux; Michèle Guillaume (Wiley, 2023)
Abstract Aim To describe nursing student self‐esteem changes over time and its impacts on learning strategies. Design Existential phenomenology. Methods Interviews were conducted in Spring 2018 in a purposive sample of 39 nursing students, exploring events critical to self‐esteem and their impacts. Transcriptions were analysed descriptively and interpretatively to decipher the process that links self‐esteem, events and learning behaviour. Results What led to self‐esteem changes were "relationships with nurses during internships" and "receiving evaluations." The students interpreted events and drew conclusions about their aptitude for nursing, which in turn prompted proactive or defensive learning behaviours. Their interpretations both depended on their self‐esteem and impacted it, in a vicious or virtuous circle. Exploring self‐esteem allows a better understanding of the importance of students' relationships with nursing teams, and of some of their defensive behaviours. Understanding the role of nursing student self‐esteem in the learning process could help improve student well‐being and competence.